Innovation in Fiberglass Ship Assembly: Social-Economic and Entrepreneurship Study of Coastal Communities - Ridwan, Mochamad; Yarsah, Waldi Novi (Jurnal AGRISEP, 2024)
The problem of low performance of fishing communities in producing capture fisheries is generally related to the low quality of the capital ships used. This research aims to reveal the factors that caused the emergence of innovation in the business of assembling fiberglass fishing ships, the level of business development, and its impact on improving the socio-economic performance of fishing communities in rural areas. The research sample included small fishing communities and a group of fishermen who had built a business assembling fiberglass fishing ships in Bengkulu Selatan Regency. Because the data collected is mostly in the form of qualitative data, the analysis method used is a descriptive-qualitative method supported by statistical analysis methods. The results indicate that the emergence of innovation in assembling fiberglass fishing ships is driven by evidence highlighting the superior quality of fiberglass over wood in ship construction. The growth of the fiberglass ship assembly business is evident through its expanding market reach and increased sales turnover. Qualitatively, the study demonstrates that the innovation in assembling fiberglass ships has a positive impact on the socio-economic performance of fishermen, manifested through improved workability, heightened work motivation, and increased capture fisheries production. Three key recommendations emerge from the findings: (1) Stakeholders should consistently support the sustainability of fiberglass ship assembly businesses; (2) Relevant agencies are encouraged to actively contribute to the substantial development of the fiberglass ship assembly sector; and (3) Fishing communities greatly benefit from socialization, empowerment, literacy, and education programs.